The archaeology of New Netherland : a world built on trade - Lukezic, Craig; McCarthy, John P. (John Patrick), 1956- (Gainesville : University Press of Florida, 2021)
This volume illuminates the influence of the Dutch empire in North America, assembling evidence from seventeenth-century settlements located in present-day New York, New Jersey, Connecticut, Pennsylvania, and Delaware.
Description based on online resource; title from digital title page (viewed on July 14, 2021).
Master record variable field(s) change: 072
Keywords: New Netherland -- Antiquities; SOCIAL SCIENCE / Archaeology; Electronic books